2019
DOI: 10.1155/2019/4586963
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Parameters in Celiac Disease: A Review on the Different Evaluation Methods and Disease Effects

Abstract: This review compiled anthropometric data from 29 original articles, published between 1995 and 2015, corresponding to a total sample of 6368 celiac disease subjects. Body mass index was the main parameter for measuring anthropometry (82.1%), followed by body mass (78.6%), body fat (51.7%), bone mineral density and bone mineral content (46.4%), and fat-free mass (44.8%). The main evaluation method was dual x-ray absorptiometry (83.3%), followed by bioimpedance (16.6%), skinfold thickness (16.6%), and isotope di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
2
10
1
2
Order By: Relevance
“…The results of the current study showed that approximately 20–30% of the children with CD were malnourished in terms of low body weight and low BMI for age. Intestinal mucosal damage in CD leads to non-optimal weight gain and malnutrition due to malabsorption of such nutrients as glucose, fatty acids, calcium, iron, vitamins, and electrolytes [ 32 , 33 ]. In addition, due to impaired nutrients absorption in patients with CD, carbohydrates oxidize more to provide energy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current study showed that approximately 20–30% of the children with CD were malnourished in terms of low body weight and low BMI for age. Intestinal mucosal damage in CD leads to non-optimal weight gain and malnutrition due to malabsorption of such nutrients as glucose, fatty acids, calcium, iron, vitamins, and electrolytes [ 32 , 33 ]. In addition, due to impaired nutrients absorption in patients with CD, carbohydrates oxidize more to provide energy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal mucosal damage in CD leads to non-optimal weight gain and malnutrition due to malabsorption of such nutrients as glucose, fatty acids, calcium, iron, vitamins, and electrolytes [ 32 , 33 ]. In addition, due to impaired nutrients absorption in patients with CD, carbohydrates oxidize more to provide energy [ 33 ]. Bardella et al maintained that weight, BMI, lean mass, and fat mass were significantly lower in patients with CD compared to the controls [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since only narrative reviews are available [ 45 , 48 , 49 , 50 ], to our knowledge, this is the first meta-analysis in the literature that assessed the changes of body composition among CD patients with and without a GFD compared to non-celiac control subjects. Nevertheless, the extensive search and the stringent selection process are the main strengths of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ряд исследователей отмечет, что дефицит массы тела встречается на фоне БГД чаще, реже отмечают ожирение, в других исследованиях нормальный ИМТ более характерен, другие не получили статически значимых отличий в группах. Allysson Costa и Gleisson A. P. Brito с обзоре антропометрических данных из 29 оригинальных исследований, опубликованных в период с 1995 по 2015 год показали, что дети с целиакией на БГД имеют более низкие показатели массы тела, чем группа сравнения [6].…”
Section: Distribution Of Patients By Body Weight In Groupsunclassified
“…После установления диагноза, динамическая оценка антропометрических данных, как основных показателей здоровья детей с целиакией необходима при каждом визите специалиста на весь период наблюдения [2,5]. Показано, что даже при соблюдении БГД могут наблюдаться нарушения физического развития [6]. Множество исследований сообщало о дефиците микронутриентов, связанном с БГД, при этом подчеркивается, что дети, независимо от того, соблюдают ли они БГД или нет, подвержены риску повышенного потребления жиров и недостаточного количества клетчатки, железа, витамина D и кальция [7].…”
Section: Introductionunclassified